ROLUL EXTRASELOR DIN PLANTELE MEDICINALE ÎN DEREGLĂRILE PANCREASULUI ENDOCRIN-GONADE - Gherman, Ion (CEP USM, 2011)
Endocrinology investigations have shown that extracts of some herbs stimulate endocrine pancreatic β cells, which remove the iodine deficiency in the body. Because herbal extracts are rich in iodine increases the work capacity, immunity,intellect, ensure the normal operation of the whole body and thyroid gland.
Keywords: plante medicinale; gonade; pancreasi endocrin; diabet zaharat